Spectrum Aggregation with Optimal Multi-Band Scheduling - Meucci, Filippo (2010)
This paper seeks to explore the integration of spectrum and network resource management functionalities to the benefit of achieving higher performance and capacity gains in an International Mobile Telecommunications-Advanced (IMT-A) scenario. In particular, we investigate the allocation of users over two frequency bands (i.e., 2 GHz and 5 GHz) for a single operator scenario. The same type of Radio Access Technology (RAT) is considered for both frequency bands. It is assumed that the operator has gained access to a non-shared 2 GHz band and to part (or all) of the frequency pool band at 5 GHz. The performance gain is analyzed in terms of higher data throughput. The performance is heavily dependent on the channel quality for each user in the considered bands which, in turn, is a function of the path loss and the distance from the Base Station (BS). The operator will have relevant improvements when Mobile Stations are heterogeneously distributed on the cell, with variable distances from the BS. A gain up to 500 kbps (20%) was obtained with the proposed optimal solution.